Transoral Closed Reduction of Fixed Atlanto-Axial Rotatory-Subluxation (AARS) in Childhood and Adolescence. Issue 5 (June 2018) - Jeszenszky, Dezsoe; Fekete, Tamas; Kleinstück, Frank; Haschtmann, Daniel; Loibl, Markus
Abstract : Atlanto-axial rotatory-subluxation (AARS) is the most common pediatric cervical spine injury. Patients usually present with contralateral rotation and inclination of the upper cervical spine after minor trauma, or associated with an infection of the upper respiratory tract. According to the authors, initial management of patients with acute and chronic AARS type I–II should comprise closed reduction and immobilization with a cervical collar or a Halo-Body-Jacket. Surgical options of open reduction or C1/2 fusion should be restricted to irreducible or recurrent subluxations. This paper reviews the detailed technique of transoral closed reduction of AARS, as well as the preoperative and postoperative considerations. Abstract : Supplemental Digital Content is available in the text.